Association between early life famine exposure and risk of metabolic syndrome in later life. Issue 10 (29th September 2022) - Zhang, Yi; Qi, Hongyan; Hu, Chunyan; Wang, Shuangyuan; Zhu, Yuanyue; Lin, Hong; Lin, Lin; Zhang, Jie; Wang, Tiange; Zhao, Zhiyun; Li, Mian; Xu, Yu; et al.
Abstract: Background: Previous studies reported that famine exposure had an effect on metabolic syndrome (MetS). However, there is an inadequacy of study regarding the association between famine exposure, adulthood general obesity, and the risk of MetS. Methods: A total of 8883 subjects aged ≥40 years from Jiading community in Shanghai were included. We defined famine exposure subgroups as nonexposed (1963–1974), fetal exposed (1959–1962), childhood exposed (1949–1958), and adolescence exposed (1941–1948). MetS was defined based on the National Cholesterol Education Program Adult Treatment Panel III (NCEP‐ATP III) criteria. Results: Compared with the nonexposed group, the risks of MetS were increased in the fetal‐, childhood‐, and adolescence‐exposed groups with odds ratios (OR) and 95% confidence intervals (CI) of 1.48 (1.23–1.78), 1.89 (1.63–2.20), and 2.34 (1.99–2.74), respectively. After adjusting for sex, age, smoking status, drinking status, education, body mass index (BMI), and physical activity, the increased risk of MetS related to the fetal‐exposed and childhood‐exposed groups with OR and 95% CI of 1.42 (1.04–1.94) and 1.50 (1.02–2.21), respectively, were observed only in women. Famine exposure was significantly associated with MetS among individuals with a BMI < 23 kg/m 2 ( p for interaction between BMI categories and famine exposure = 0.0002 in the whole cohort), while there existed a gender difference ( p  = 0.0023 in females, p  = 0.4484 in males). When evaluating the joint effects of the combination of famine exposure in early life and general obesity in adulthood on MetS, we observed the highest estimate in participants with both adulthood general obesity and fetal famine exposure (OR 17.52; 95% CI, 10.07–30.48) compared with those without famine exposure nor adulthood obesity. Conclusions: Obesity in adulthood significantly further aggravated the risk of MetS in individuals who experienced early life undernutrition, especially in females. Abstract : Highlights In a community‐dwelling Chinese population, famine exposure in early life, especially during the fetal and childhood stages, has an association with an increased risk of metabolic syndrome (MetS) in later life, but the above findings only applied to females, not males. Compared to nonexposed and nonobese participants, those with both fetal famine exposure and adulthood general obesity had a higher risk of MetS of more than 17‐folds. The coexistence of malnutrition in early life and adulthood overweight/obesity had an association with a higher risk of MetS. 摘要: 背景: 以前的研究报道了饥荒暴露对代谢综合征(MetS)有影响。然而, 关于饥荒暴露、成年期肥胖和 MetS 风险之间的关系则较少研究。 方法: 纳入上海市嘉定社区年龄 > 40岁的8883名受试者。我们将饥荒暴露亚组定义为未暴露(1963‐1974)、胎儿暴露(1959‐1962)、儿童暴露(1949‐1958)和青春期暴露(1941‐1948)。 MetS根据 NCEP‐ATP III标准定义。 结果: 与未暴露组相比, 胎儿、儿童和青春期暴露组的 MetS 风险增加, OR 和 95% CI 分别为 1.48 (1.23‐1.78)、1.89 (1.632.20) 和 2.34 (1.99‐ 2.74)。在校正性别、年龄、吸烟状况、饮酒状况、教育程度、体重指数(BMI)和体力活动后, 女性中观察到胎儿暴露组和儿童暴露组发生 MetS 的风险增加, OR 和 95%CI 分别为 1.42( 1.04‐1.94) 和 1.50 (1.02‐2.21)。在 BMI<23 kg/m 2 的个体中, 饥荒暴露与 MetS 显着相关(整个队列中 BMI 类别与饥荒暴露之间的交互作用 P = 0.0002), 但存在性别差异(女性 P=0.0023, 男性P=0.4484)。在评估生命早期饥荒暴露和成年期肥胖对 MetS 的联合影响时, 我们观察到与没有饥荒暴露或成年肥胖的人相比, 成年肥胖和胎儿饥荒暴露的参与者有最高估计值(OR, 95%CI:17.52, 10.07‐ 30.48)。 结论: 成年期肥胖显著加剧了早年营养不良个体(尤其是女性)发生 MetS 的风险。